Clean and healthy living behavior and diarrhea among children: A cross-sectional study in Duria Village, West Nias - Sibagariang, Eva Ellya; Simanjuntak, Mafe Robbi; Waruwu, Nestapa Viatni (Buletin Kedokteran & Kesehatan Prima, 2025)
Diarrheal disease remains a critical public health concern, especially in developing countries like Indonesia, where it significantly contributes to morbidity and mortality among young children. This study aimed to analyze the relationship between Clean and Healthy Living Behaviors (CHLB) and the incidence of diarrhea among children aged 7-10 years in Duria Village, West Nias. A cross-sectional study was conducted from January to February 2024, involving 35 mothers of children aged 7–10 years with diarrhea, selected through purposive sampling. Data were collected using questionnaires to assess handwashing behavior, access to clean water, latrine conditions, and garbage disposal practices. The results indicated that while handwashing habits, latrine conditions, and garbage disposal practices did not show statistically significant associations with diarrhea prevalence, access to clean water had a highly significant association (p < 0.001), albeit counterintuitively suggesting that access to clean water is associated with increased diarrhea. These unexpected findings warrant further investigation to understand potential confounding factors. The study underscores the complex interplay between CHLB and diarrheal disease, highlighting the need for targeted interventions to improve sanitation and hygiene practices in Duria Village.